Tindak Tutur Ilokusi Direktif dalam Interaksi Pembeli dan Penjual Online Shop di Shopee Live - Astri, Nanda Dwi; Panggabean, Kristina; Nasution, Arie Azhari (GERAM, 2024)
In the digital era, interaction in online buying and selling transactions is a key element in building effective communication between sellers and buyers. One form of communication that has a significant role in e-commerce is directive illocutionary speech acts, which are used to influence the actions of speech partners. However, studies on the usage pattern of this speech act in the context of live streaming are still limited. Therefore, this study aims to identify and analyze the types and functions of directive illocutionary speech acts that appear in the interaction between sellers and buyers on Shopee Live. Using a qualitative descriptive approach, this study collected data from observation and recording of conversations on Shopee Live sessions within a certain time span. The results showed that the five types of directive illocutionary speech acts found include ordering, commanding, requesting, recommending, and advising. Of the five types, the speech act of recommendation is most dominantly used, while the speech act of advising is least common. The findings indicate that in online buying and selling transactions, sellers tend to use recommendation strategies to attract buyers' attention and increase their interest in the product. This study contributes to the development of pragmatics studies in digital communication and can be used as a reference for e-commerce businesses in designing more effective communication strategies on live streaming platforms.